The impact of electronic marketing on crisis management"A field study on employees of popular credit Bank in Syria - General Administration" (Damascus University Journal for the economic and Political sciences, 2025)
This study aimed to study the impact of e-marketing dimensions (e-service, e-pricing, e-promotion, e-distribution) on crisis management from the point of view of employees of popular credit Bank - General Administration. The researcher used the descriptive approach, and adopted the questionnaire as a tool for the study, which was distributed to a sample of /192/ bank workers. /183/ questionnaires were retrieved, of which /179/ questionnaires were valid for statistical analysis, and the appropriate statistical tests were conducted using the SPSS27 program. The study reached results, the most important of which are: The level of electronic marketing in the bank under study reached the average level. It also showed that there was interest in crisis management in the bank under study, but not at an acceptable level. It was also shown that there is a statistically significant effect of e-marketing and all its dimensions represented by (e-service, e-pricing, e-promotion, e-distribution) on crisis management. The researcher presented a set of recommendations, the most important of which are: the necessity of greater adoption of electronic marketing by the bank due to its major role in managing crises effectively, working to expand the electronic services provided by the bank, and ensuring that they meet the banking needs and requirements of customers.
Keywords: E-Marketing; Crisis Management; Popular Credit Bank